PREVALENCE OF DEPRESSION AND ANXIETY IN A VILLAGE IN SINDH - Luni, Faraz Khan; Ansari, Briha; Jawad, Ahmed; Dawson, Amber; Baig, Shahid Masud (Journal of Ayub Medical College Abbottabad, 2009)
Objective: To study the prevalence of Anxiety and Depression and its association in a rural area of Sindh, Pakistan. Methods: A cross-sectional study was conducted at Ansari Para, in Tehsil Hala, Sindh province in Pakistan, using the Aga Khan University Anxiety and Depression Scale Urdu Version. Results: Out of a total of 260 people interviewed, 112 people (43.1%) were screened to have anxiety and depression. Depression and anxiety were strongly associated with female gender, family dynamics, child environment, unsuccessful love affairs and among those with medical chronic disorders. A gradual decreasing incidence of depression and anxiety was noted with increasing level of education. A significantly strong association was noted between child mortality and maternal depression while no such association was found in males. There is a significant difference in the age of depressed and normal individuals. There was significant correlation between unhappy childhood and unsatisfying family relationships. However, no relationships were found between depression & anxiety and martial status, presence or number of children, absence of male offspring, living in joint family system, financial problems and any deficiencies that the respondents felt that he might have. Conclusion: This study suggests that anxiety and depression is a common psychiatric disorder even in remote village areas and contradicts the common belief that people those who live in the remote rural areas lead stress-free lives or have low rates of psychiatric morbidity. Keywords: Prevalence, Depression, Anxiety, Rural, Sindh